Reviews and Responses for Hidden Markov Models and Flight Phase Identification - Arts, Emy; Fala, Nicoletta; Sun, Junzi; Perrichon, Rémi; Gendre, Xavier; Klein, Thierry (Journal of Open Aviation Science, 2024)
See detailed reviews and responses in the PDF file. DOI for the original paper: https://doi.org/10.59490/joas.2024.7269